Calorimetry, Morphometry, Oxidative Stress, and Cardiac Metabolic Response to Growth Hormone Treatment in Obese and Aged Rats - Seiva, F. R. F. [UNESP]; Chuffa, L. G. A. [UNESP]; Ebaid, Geovana Xavier [UNESP]; Silva, T. [UNESP]; Fernandes, A. A. H. [UNESP]; Novelli, E. L. B. [UNESP] (Georg Thieme Verlag Kg, 2011)
This study investigated the effects of growth hormone therapy on energy expenditure, lipid profile, oxidative stress and cardiac energy metabolism in aging and obesity conditions. Life expectancy is increasing in world population and with it, the incidence of public health problems such as obesity and cardiac alterations. Because growth hormone (GH) concentration is referred to be decreased in aging conditions, a question must be addressed: what is the effect of GH on aging related adverse changes? To investigate the effects of GH on cardiac energy metabolism and its association with calorimetric parameters, lipid profile and oxidative stress in aged and obese rats, initially 32 male Wistar rats were divided into 2 groups (n = 16), C: given standard-chow and water; H: given hypercaloric-chow and receiving 30 % sucrose in its drinking water. After 45 days, both C and H groups were divided into 2 subgroups (n = 8), C + PL: standard-chow, water, and receiving saline subcutaneously; C + GH: standard-chow, water, and receiving 2 mg/kg/day rhGH subcutaneously; H + PL: hypercaloric-chow, 30 % sucrose, receiving saline subcutaneously; H + GH: hypercaloric-chow, 30 % sucrose, receiving rhGH subcutaneously. After 30 days, C + GH and H + PL rats had higher body mass index, Lee-index, body fat content, percent-adiposity, serum triacylglycerol, cardiac lipid-hydroperoxide, and triacylglycerol than C + PL. Energy-expenditure (RMR)/body weight, oxygen consumption and fat-oxidation were higher in H + GH than in H + PL. LDL-cholesterol was highest in H + GH rats, whereas cardiac pyruvate-dehydrogenase and phosphofrutokinase were higher in H + GH and H + PL rats than in C + PL. In conclusion, the present study brought new insights on aging and obesity, demonstrating for the first time that GH therapy was harmful in aged and obesity conditions, impairing calorimetric parameters and lipid profile. GH was disadvantageous in control old rats, having undesirable effects on triacylglycerol accumulation and cardiac oxidative stress.
Keywords: growth hormone; obesity; aging; cardiac energy metabolism